PENGARUH MINAT MEMBACA DAN PENGUASAAN KOSAKATA TERHADAP KEMAMPUAN MENULIS CERPEN KELAS VI SD NEGERI 68 PALEMBANG - Yessi Fitriani (Jurnal Pembahsi (Pembelajaran Bahasa Dan Sastra Indonesia), 2018)
This study aims to determine the significant effect of (1) reading interest on short story writing, (2) the influence of vocabulary on short story writing, and (3) reading interest and vocabulary mastery together on the ability to write short stories. This research was carried out at 68 Public Elementary Schools in Palembang in July 2017 to September 2017. The research method used in this study was quantitative research methods through comparative causal. The population of this study is all students of class VI SD Negeri 68 Palembang. The sample of the research in this study is a randomly selected VI student with a total of 40 students. Data analysis was carried out with the analysis used to test hypotheses regarding the presence of significant influence 0.05 obtained constant values of 23, 262 and the coefficient of the variable regression line equation (X1) of 0.384 and the vocabulary mastery variable (X2) of 0, 343, so it was obtained the equation of the regression line between variables X1 and X2 is y = 23, 262 + 0, 384 X1 + 0, 343 X2. The regression equation identifies that if the reading interest variable and vocabulary mastery variables are increased by 1 unit, then the Y value increases by 0, 384 + 0, 343 = 0, 727. Keywords— Effect of Reading Interest and Vocabulary Mastery on Writing Short Stories